SPECTROPHOTOMETRIC DETERMINATION OF MOLYBDENUM CONTENT IN 99mTc SOLUTION VIA Mo-TGA-KSCN COMPLEXES FORMATION - Muhamad Basit Febrian; Titin Sri Mulyati; Ade Suherman; Natalia Adventini; Yanuar Setiadi; Duyeh Setiawan; Azmairit Aziz (BATAN, 2018)
SPECTROPHOTOMETRIC DETERMINATION OF MOLYBDENUM CONTENT IN 99mTc SOLUTION VIA Mo-TGA-KSCN COMPLEXES FORMATION. Quality of Technetium-99m solution is determined from its radiochemical, radionuclidic and chemical purity. One of the major concern about chemical purity of Tc-99m from irradiated natural molybdenum is its molybdenum content or Mo breaktrough. Spectrophotometric method is one of method that could be applied for Mo determination in Tc-99m solution. Molybdenum (V) could form a colored complexes with potassium thiocyanate (KSCN) but Molybdenum (VI) must be reduced before formed a complexes with KSCN. Thioglycolic Acid (TGA) was used as reducing agent to obtain reduced Mo (Mo(V)). A series of optimization process was carried out to find optimum condition of complex formation for analysis purposes. Optimized condition were 3 mL of 25% HCl was added into a volume of Mo sample, followed by 200 µL of 10% TGA, 1 mL of 10% KSCN, and water addition up to 10 mL total volume. The method is linear over 2 ppm to 30 ppm Mo with regression coeffisient 0.9988±0.0007. The detection limit was 0.212 ppm Mo. Color of the complex has a stability of absorbance up to 120 minutes while stored at room temperature. No significant deviation occured when 1000 ppm of oxalic acid, methyl ethyl ketone and iron added into sample solution. This complexing method is suitable for spectrophotometric determination of molybdenum content in Tc-99m solution as a part of quality control process.